PERANCANGAN SISTEM KOORDINASI DAN KENDALI FORMASI UAV QUADROTOR UNTUK OPTIMALISASI MITIGASI BENCANA - Pujantoro Tnunay, Ishak Hilton; Abdurrohman, Muhammad Qodar; Awwalur Rizqi, Ahmad Ataka; Faris, Muhammad; Puspita Sari, Dwi Retno (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Indonesia is located between 2 continental plates in which causes the disaster often happens. One of the solution to encounter the mapping and searching after disaster is employing UAV robots. Quadrotor is one of these underlying robots that widely used due to its highly maneuverability, cheap, and less run-way. Instead of using single quadrotor which is less efficient and needs more time, we use multi-quadrotor system. These agents will coordinate to each other and form a formation, thereby it can be used to optimize the disaster monitoring process by multi-quadrotor. This work begins as follows: The study of formation and coordination of multi UAV system.Â Afterwards, we design the path-planning and formation control algorithm based on potential fields for Quadrotor. Otherwise, we also employ visual navigation method combined with GPS in quadrotor to obtain its global position. In simulation, it can be showed that our approach works well. in the future we will apply it entirely in real quadrotor. Moreover, the results of this research have been published in some international conference, even receive a best paper award as well.Â Keywords: Â Disaster Monitoring, Quadrotor, Visual Navigation, Path Planning, Formation Control